Using Commonplace Books to Enrich Medieval and Renaissance Courses - Parker, Sarah E.; Silva, Andie (Teaching the Medieval Ages - ARC, 2023)
This book is a collection of essays offering a wide range of approaches to teaching with commonplace books. In the medieval period and beyond, commonplace books promoted a blend of excerpting, memorization, creative writing, and journaling, making them the analogue equivalent to modern-day digital journaling, bookmarking, and note-taking tools. Covering a variety of methods for introducing students to the medieval and Renaissance reading practice known as commonplacing, this volume provides instructors with concrete guidelines for using commonplace books as a teaching and learning tool. The enclosed essays provide a point of reference for best practices as well as concrete models for teaching and learning with commonplace books, helping instructors develop more student-centred, inclusive curricula.